Characteristic distribution and possible roles of waves around the lower hybrid frequency in the magnetotail reconnection region. Issue 10 (18th October 2014) - Zhou, Meng; Li, Huimin; Deng, Xiaohua; Huang, Shiyong; Pang, Ye; Yuan, Zhigang; Xu, Xiaojun; Tang, Rongxin
Abstract It has long been suggested that waves around the lower hybrid frequency play a significant role in magnetic reconnection. In this paper we statistically study the distribution and possible roles of waves around lower hybrid frequency based on the wave data recorded by the Cluster spacecraft during 21 magnetotail reconnection events. We find that, as the plasma β increments, magnetic field fluctuations associated with waves increase while electric field fluctuations decrease. As β exceeds 10, both magnetic and electric field fluctuations decrease. Furthermore, a two‐dimensional wave distribution is constructed based on the two‐dimensional reconnection model. The most intense magnetic field fluctuations occur in the outflow region, while they are weaker in the inflow region and separatrix region. The most intense electric field fluctuations occur around the separatrix region, while they are weaker in the inflow and outflow regions. There are positive correlations between wave strength and energetic electron acceleration, as well as between wave strength and reconnection rate. Our results may be important for fully understanding the role of waves around lower hybrid frequency in the dissipation process of magnetic reconnection.